Analisis Determinan Kinerja Pelaksanaan Anggaran Satuan Kerja di Kalimantan Timur - Parno, Parno (Direktorat Sistem Perbendaharaan, 2024)
This study aims to analyze the determinants of budget execution performance of spending units in East Kalimantan. Budget execution, as an exogenous variable, is proxied by goods and services procurement, external factors, and activity implementation. The analysis model for budget execution performance is constructed using the Structural Equation Modeling Partial Least Square (SEM PLS) method. The results showed that the exogenous variable of goods and services procurement significantly influences activity implementation. However, goods and services procurement and external factors directly do not have a significant impact on budget execution performance. Conversely, goods and services procurement through the implementation of activities demonstrates a significant effect on budget execution performance.